CRITICAL RELIGIOUS LITERACY IN ISLAMIC RELIGIOUS EDUCATION: STRENGTHENING RATIONALITY, ETHICS, AND FAITH IN THE POST-TRUTH ERA - Okta Khairul Hikmah; Syaiful Hadi (Program Studi Pendidikan Agama Islam, 2026)
Islamic Religious Education (PAI) plays a strategic role in shaping students’ religious character within the context of Indonesia’s plural society. Current challenges such as the rise of religious extremism, social polarization, and widespread misconceptions about Islamic teachings exacerbated by digital media demand a comprehensive educational framework that fosters religious moderation. This study aims to construct a conceptual model of PAI learning based on religious moderation by examining the Islamic principles of wasathiyah, reconstructing curriculum content, identifying supportive pedagogical approaches, clarifying the teacher’s role, and synthesizing these elements into a coherent theoretical framework. This research employs a qualitative design using a library research approach. Data were collected from classical Islamic texts, contemporary scholarly works, official policy documents, and relevant academic articles. The analysis was conducted through data reduction, thematic categorization, and theoretical synthesis using content analysis techniques. The study focuses on conceptual development rather than empirical testing. The findings reveal that the principles of religious moderation including justice, balance, tolerance, and anti-extremism are firmly rooted in Islamic teachings and serve as essential foundations for PAI instruction. The PAI curriculum needs to be reconstructed to become more inclusive, contextual, and grounded in diverse Islamic scholarly traditions in order to cultivate comprehensive religious understanding. Pedagogically, dialogic, reflective, collaborative, and experiential learning approaches are effective in fostering moderate religious awareness among students. Teachers function not only as knowledge transmitters but also as moral exemplars, facilitators, and agents of moderation who shape the school’s religious climate. These four domains are synthesized into a conceptual model for PAI instruction that encompasses foundational values, curriculum reconstruction, pedagogical strategies, teacher roles, and supportive learning environments. The post-truth era is characterized by the massive circulation of information, the weakening of knowledge authority, and the dominance of emotion over rational judgment. These conditions significantly influence the religious sphere, including Islamic Religious Education (PAI), which now faces challenges such as religious misinformation, digital radicalism, and sentiment based polarization. This article aims to analyze the concept of critical religious literacy as a foundation for strengthening rationality, ethics, and faith within PAI instruction. This study employs a literature review method by examining works related to critical literacy, Islamic education, cognitive theory, and the dynamics of the post-truth era. The findings indicate that critical religious literacy is essential as a framework that harmonizes reason and faith, builds moral sensitivity, and enhances students’ ability to evaluate religious information responsibly. Strengthening rationality improves verification and analytical skills; the ethical dimension guides moral conduct; and faith provides spiritual stability amid information disruption. This study concludes that integrating these three dimensions is a fundamental strategy to develop learners who are not only critical thinkers but also ethical and spiritually grounded. Therefore, critical religious literacy serves as a relevant and strategic approach to reinforcing cognitive and spiritual resilience among Muslim learners in today’s post-truth context.